Performance of four fish pass installations recently built on two rivers in South-west France - Travade, F.; Larinier, M.; Boyer Bernard, S.; Dartiguelongue, J. (HAL CCSD, 1998)
During the 1970s, a number of projects were initiated in France directed towards the conservation and rehabilitation of migratory fish stocks. Stemming from these efforts, four relatively large fish passes were built between 1984 and 1989 on the Garonne and Dordogne rivers in south west France. Two are pool-type fish passes (one with a double vertical slot at Bergerac on the Dordogne river, and the other with a single vertical slot at Le Bazacle on the Garonne river) the other two are fish elevators (Golfech on the Garonne river and Tuilières on the Dordogne river). This chapter describes the characteristics and operating constraints of each installation. Since construction, operations have been monitored on a more or less (dependent on site) constant basis using a semi-automated video counting device which provides precise data on the quantity and timing of fish passage. The four installations have enabled passage of some 30 fish species, including migratory diadromous populations of Atlantic salmon Salmo salar, sea-run brown trout Salmo trutta, allice shad Alosa alosa, European eel Anguilla anguilla, sea lamprey Petromyzon marinus, and a number of so-called "sedentary" species such as roach Rutilus rutilus, bream Abramis brama, and barbel Barbus barbus for which very clear migration rythms have been nonetheless observed. Passage of allice shad, which has often been difficult to achieve over traditional fish passes, has been found satisfactory in both the pool and elevator installations, with annual passage of several tens of thousands of individuals (80 000 to 86 000 shad at the Tuilières and Golfech fish elevators in 1995). The relative effectiveness of each type of pass is discussed in relation to the various migratory species. Finally, the main results concerning the seasonal and daily migratory rythms of various diadromous and resident species are presented.